Indoleamine 2,3-Dioxygenase Cannot Inhibit Chlamydia trachomatis Growth in HL-60 Human Neutrophil Granulocytes - Virok, Dezső P.; Tömösi, Ferenc; Keller-Pintér, Anikó; Szabó, Kitti; Bogdanov, Anita; Poliska, Szilárd; Rázga, Zsolt; Bruszel, Bella; Cseh, Zsuzsanna; Kókai, Dávid; Paróczai, Dóra; Endrész, Valéria; et al. (Frontiers in Immunology, 2021)
Aims: Neutrophil granulocytes are the major cells involved in the Chlamydia trachomatis (C. trachomatis)-mediated inflammation and histopathology. A key protein in human intracellular antichlamydial defense is the tryptophan degrading enzyme indoleamine 2,3-dioxygenase (IDO) which limits the growth of the tryptophan auxotroph Chlamydia. Despite its importance, the role of IDO in the intracellular defense against Chlamydia in neutrophils is not well characterized. Methods: Global gene expression screen was used to evaluate the effect of C. trachomatis serovar D infection on the transcriptome of human neutrophil granulocytes. Tryptophan metabolite concentrations in the Chlamydia infected and/ or interferon-gamma (IFNG) treated neutrophils were measured by Ultra High Performance Liquid chromatography–tandem Mass Spectrometry (UHPLC-MS/MS). Results: Our results indicate that the C. trachomatis infection had a major impact on the neutrophil gene expression inducing 1295 genes and repressing 1510 genes. A bioinformatics analysis revealed that important factors involved in the induction of neutrophil gene expression were the interferon-related transcription factors such as IRF1-5, IRF7-9, STAT2, ICSB and ISGF3. One of the upregulated genes was ido1, a known infection and interferon-induced host gene. The tryptophan degrading activity of IDO1 was not induced significantly by Chlamydia infection alone, but the addition of IFNG greatly increased its activity. Despite the significant IDO activity in IFNG treated cells, the C. trachomatis growth was not affected by IFNG. This result was in contrast to what we observed in HeLa human cervical epithelial cells, where the IFNG-mediated inhibition of C. trachomatis growth was significant and the IFNG-induced IDO activity correlated with the growth inhibition. Conclusions: IDO activity was not able to inhibit chlamydial growth in human neutrophils. Whether the IDO activity was not high enough for inhibition or other chlamydial growth promoting host mechanisms were induced in the infected and interferon-treated neutrophils need to be further investigated.